Pengaruh Faktor Emosional dan Faktor Rasional Terhadap Keputusan Mahasiswa dalam Memilih Produk Bank Syariah Indonesia (Studi Pada Mahasiswa Universitas Islam Malang) - Sabariah Sabariah; Nur Diana; Harun Alrasyid (El-Aswaq, 2022)
This research analyzes the influence of emotional and rational factors on student decisions to chooseIndonesian Islamic Bank products at the University of Islam Malang students. The sample in this study was 99students of the Islamic University of Malang. Data was collected by distributing questionnaires. Analysis of thedata used in this study using validity test, reliability test, normality test, multicollinearity, heteroscedasticity,simultaneous F test, coefficient of determination, and t-test. The results of this study show that variableemotional factors and rational factors significantly affect the decision to choose a product. While partially 1)the emotional factor variable partially has a significant and positive effect on the decision to choose a product,2) the rational factor variable partially has a significant and positive effect on the decision to choose a product.